Personal Awareness According to Johari Window For Youth and Sport Forum Mangers In Baghdad From the Employees’’ Point of View - Wahab, Salah; Ali, Jasim (Journal of Physical Education, 2018)
Personal Awareness According to Johari Window For Youth and Sport Forum Mangers In Baghdad From the Employees’’ Point of View The study aimed to build a measure of personal awareness in accordance with the window of Johari for managers of youth and sports forums in Baghdad, and identify the level from the point of view of workers, the problem lies in the attempt of the researcher to answer a specific question is: Do managers of the youth forums and sports in Baghdad, To create an atmosphere of human interaction and harmony with employees? . The researcher followed the descriptive research method in the method of associative relationships on a sample of the continuous employees in the Baghdad governorate for the year 2018 of 608 individuals who were chosen by a vertical percentage of 62.875% of the original society for the period from 14/12/2017 to 5/4. (308), and sample application (298). After a series of logical procedures in constructing measurement tools in sport management according to the measurement parameters The scale of the study was constructed and then applied to the application sample and its results were processed using the pouch system Statistical (SPSS), the researcher concludes that the personal consciousness according to Johari Window Managers Youth and Sports Forum was not to be required to have a level.